A Comparison of Registered and Unregistered Female Sex Workers in Tijuana, Mexico - Sirotin, Nicole (Association of Schools of Public Health, 2010)
OBJECTIVE: Sex work is regulated in Tijuana, Mexico, but only half of the city's female sex workers (FSWs) are registered with the municipal health department, which requires regular screening for sexually transmitted infections (STIs) and human immunodeficiency virus (HIV). We examined correlates of registration to determine if it confers measurable health benefits. METHODS: From 2004 to 2006, we interviewed FSWs in Tijuana ≥18 years of age who reported recent unprotected sex with at least one client and were not knowingly HIV-positive, and tested them for HIV, syphilis, gonorrhea, and chlamydia. Logistic regression identified factors associated with registration. RESULTS: Of 410 FSWs, 44% were registered, 69% had been tested for HIV, 6% were HIV-positive, and 44% tested positive for any STI. Compared with unregistered FSWs, registered FSWs were more likely to have had HIV testing (86% vs. 56%, p<0.001) and less likely to test positive for any STI (33% vs. 53%, p<0.001) or HIV (3% vs. 8%, p=0.039). Factors independently associated with registration included ever having an HIV test (adjusted odds ratio [AOR] = 4.19) and earning >$30 per transaction without a condom (AOR=2.41), whereas working on the street (AOR=0.34), injecting cocaine (AOR=0.06), snorting or smoking methamphetamine (AOR=0.27), and being born in the Mexican state of Baja California (AOR=0.35) were inversely associated with registration. CONCLUSION: Registered FSWs were more likely than unregistered FSWs to have had HIV testing and to engage in less drug use, but did not have significantly lower HIV or STI prevalence after adjusting for confounders. Current regulation of FSWs in Tijuana should be further examined to enhance the potential public health benefits of registration.